О построении математических моделей объемного напряженно-деформированного состояния конических колес с круговой формой зубьев - Иванова, З.А.; Иванов, Е.М.; Божко, А.Е. ("Доповіді НАН України", 2007)
A theory of the structure of an approximate solution of the problem of determination of the fields of bending stresses in circular gears of conic wheels is developed.